First Observation of CP Violation and Measurement of Polarization in B^{+}→ρ(770)^{0}K^{}(892)^{+} Decays. - Aaij,R; Abdelmotteleb,ASW; Abellan,Beteta C; Abudinén,F; Ackernley,T; Adefisoye,AA; Adeva,B; Adinolfi,M; Adlarson,P; Agapopoulou,C; Aidala,CA; Ajaltouni,Z; et al. (Phys Rev Lett, 2026)
An amplitude analysis of the B^{+}→(π^{+}π^{-})(K_{S}^{0}π^{+}) decay is performed in the mass regions 0.30<m_{π^{+}π^{-}}<1.10  GeV/c^{2} and 0.75<m_{K_{S}^{0}π^{+}}<1.20  GeV/c^{2}, using pp collision data recorded with the LHCb detector corresponding to an integrated luminosity of 9  fb^{-1}. The polarization fractions and CP asymmetries for B^{+}→ρ(770)^{0}K^{}(892)^{+} decays are measured. Violation of the CP symmetry in the decay B^{+}→ρ(770)^{0}K^{}(892)^{+} is observed for the first time, with a significance exceeding 9 standard deviations. The CP asymmetry is measured to be A_{CP}=0.507±0.062(stat)±0.024(syst) and the CP-averaged longitudinal polarization fraction of f_{L}=0.720±0.028(stat)±0.009(syst). The measurements help to shed light on the polarization puzzle of B mesons decaying to two vector mesons.